การผลิตไฟฟ้าโดยระบบเทอร์โมโฟโต้โวลเทซ ELECTRICITY GENERATING BY THERMOPHOTOVOLTAIC SYSTEM มาน - สุขละมัย, มานนท์ (Srinakharinwirot University Journal of Sciences and Technology, 2015)
บทคัดย่อ บทความนี้เป็นการนำเสนออีกหนึ่งเทคโนโลยีในการผลิตไฟฟ้าโดยใช้วัสดุกึ่งตัวนำที่มีแถบช่องว่างพลังงานตำ่เป็นตัวเปลี่ยนพลังงานรังสีความร้อนเป็นพลังงานไฟฟ้า ซึ่งเรียกกันโดยทั่วไปว่าระบบผลิตไฟฟ้าแบบเทอร์โมโฟโต้โวลเทซโดยได้กล่าวถึงหลักการทำงานและองค์ประกอบพื้นฐานของระบบและองค์ประกอบอื่นๆ ทั้งที่ได้ทำการศึกษาทดลองไปแล้ว ที่ยังอยู่ในขั้นของการทดลองในห้องวิจัย และทั้งที่ยังเป็นข้อเสนอในทางทฤษฎีอันจะสามารถช่วยเพิ่มประสิทธิภาพโดยรวมของระบบได้รวมไปถึงจุดเด่น จุดด้อย และข้อจำกัดของระบบผลิตไฟฟ้าแบบเทอร์โมโฟโต้โวลเทซนี้ การพัฒนาการนำระบบเทอร์โมโฟโต้โวลเทซไปประยุกต์ใช้และทิศทางในการศึกษาวิจัยเพื่อเพิ่มประสิทธิภาพในการเปลี่ยนรูปพลังงานของระบบผลิตไฟฟ้าแบบเทอร์โมโฟโต้โวลเทซให้เหมาะสมกับการนำไปใช้งาน Abstract This paper presents an alternative method in electricity generation by using semiconductor material which has low band gap energy to convert radiant heat energy into electric energy; it is known-well as thermophotovoltaicpower generation system. The paper is summarizing explained about principle of system operation and its basic components, also the further components that some of them are already done, some of them are in progress in laboratory, and some of them are just in theory aspect that it would help to improve the overall system efficiency, the advantages, disadvantages and limits of the thermophotovoltaic system, new developments in thermophotovoltaic technology and their applications, also the suitable research direction on improving the energy conversion efficiency of the thermophotovoltaic system with suitable application.